1994
DOI: 10.1007/bf01984125
|View full text |Cite
|
Sign up to set email alerts
|

The non-contraceptive effects of the levonorgestrel-releasing intrauterine device

Abstract: Clinical trials have consistently shown that the IUD that releases 20 micrograms levonorgestrel daily (LNG-IUD-20) has a contraceptive efficacy comparable to, if not surpassing, the Copper T380 and the Multiload Copper-375 IUDs. The focus of this review is the device's non-contraceptive effects--the beneficial ones, such as reduction of menorrhagia, a therapeutic effect on dysmenorrhea, and prevention of ectopic pregnancy, as well as the deleterious ones, such as amenorrhea, spotting and irregular bleeding, ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
1

Year Published

1997
1997
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 36 publications
1
9
1
Order By: Relevance
“…Although both methods seem to be equally effective in reducing MBL, ER is an invasive procedure requiring operative equipment and an operation theatre, while the placement of the LNG-IUS can be carried out in the outpatient department. This is in line with other studies that found that 64% of 28 women scheduled for hysterectomy due to bleeding problems could cancel their decision to undergo hysterectomy, compared with 14% in the control group [19]. Another aspect is the reversibility of the treatment and potential return of fertility associated with the LNG-IUS.…”
Section: Discussionsupporting
confidence: 90%
“…Although both methods seem to be equally effective in reducing MBL, ER is an invasive procedure requiring operative equipment and an operation theatre, while the placement of the LNG-IUS can be carried out in the outpatient department. This is in line with other studies that found that 64% of 28 women scheduled for hysterectomy due to bleeding problems could cancel their decision to undergo hysterectomy, compared with 14% in the control group [19]. Another aspect is the reversibility of the treatment and potential return of fertility associated with the LNG-IUS.…”
Section: Discussionsupporting
confidence: 90%
“…Moreover, we included unilocular cysts with anechoic cyst contents only if their mean diameter was > 35 mm. Despite this, our results confirm that functional cysts are less common among users of the COC pill and more common among women using a gestagen IUD than among women with spontaneous menstrual cycles. The higher rate of persisting ovarian masses in our study than in the other two is difficult to explain.…”
Section: Discussioncontrasting
confidence: 64%
“…The levonorgestrol‐releasing intrauterine contraceptive device has added a new dimension to the medical treatment of menorrhagia 45 .…”
Section: Introductionmentioning
confidence: 99%